KNOWLEDGE AND ATTITUDES OF STUDENTS ON FIRST AID, CARDIOPULMONARY RESUSCITATION AND AUTOMATED EXTERNAL DEFIBRILLATOR - Savić, Ljiljana; Savić, Marko; Kucurski, Ljubiša; Srđan, Srđan; Nikolić, Jagoda (PONS - medicinski časopis, 2024)
Cardiac arrest is the leading cause of death in Europe with around 700,000 cases per year. With the use of modern technology, the mortality rate has decreased, but the general population’s lack of education about cardiopulmonary resuscitation (CPR) and the use of an automatic external defibrillator (AED) is still a problem. During their academic education, students of the College of Health Sciences Prijedor meet in theoretical and practical classes with CPR and the use of AEDs from various subjects. Aim: The aim of the research is to examine the knowledge and attitudes of students about providing first aid, resuscitation and proper use of AED. Respondents and methods: The research was conducted in 2023 using an anonymous questionnaire taken from author Mikac Lee, which was culturally adapted. Eighty six in-class students of the College of Health Sciences Prijedor participated in the research. The questionnaire consists of sociodemographic data, knowledge of first aid and CPR, as well as the use of AED. The results were processed using SPSS V26 and presented tabularly and graphically. Results: The results showed that most students of all study programs would properly approach a vulnerable person. There was no statistically significant difference in knowledge of the examined items between students of different study programs. Students were divided on the claim that every person is legally obliged to provide first aid to an injured person. Conclusion: It is important to focus attention on the education of other non-medical students, because cardiac arrest can happen anywhere and to anyone, and the environment of the person at risk is a key factor in the survival rate of the person at risk. A high level of education of the population in the field of first aid, resuscitation and the use of AEDs is one of the biggest goals of all health workers.